2022
DOI: 10.3390/cells11081371
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variations and mRNA Expression of Goat DNAH1 and Their Associations with Litter Size

Abstract: Dynein Axonemal Heavy Chain 1 (DNAH1) encodes proteins which provide structural support for the physiological function and motor structure of spermatozoa (hereafter referred to as sperm) and ova. This study found that three single nucleotide polymorphisms (SNPs), the 27-bp insertion/deletion (InDel) mutations and three exonic copy number variations (CNVs) within DNAH1 were significantly associated with litter size of Shaanbei white cashmere goats (n = 1101). Goats with the wildtypes of these three SNPs had hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…qPCR was performed using SYBR Green Real-time PCR Master Mix (TaKaRa, China). 2 −ΔΔCt method and Student's t tests were used for comparative analysis of gene differential expression ( Wang et al, 2022a , b ). p < 0.05 and p < 0.01 were considered significant and highly significant, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…qPCR was performed using SYBR Green Real-time PCR Master Mix (TaKaRa, China). 2 −ΔΔCt method and Student's t tests were used for comparative analysis of gene differential expression ( Wang et al, 2022a , b ). p < 0.05 and p < 0.01 were considered significant and highly significant, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Reproductive performance directly affects the economic benefits of goat farming, and the ovary, as an organ for oocyte production and reproductive hormone secretion, is directly related to litter size traits [ 2 , 3 ]. Existing studies have identified several genes associated with litter size traits in goats, such as DNAH1 [ 4 ], CFAP43 [ 5 ], CTSS [ 6 ], EPHA6 [ 7 ], and POU1F1 [ 8 ]. However, the key molecular regulatory mechanisms remain unclear.DNA methylation (DNAm) is a type of epigenetic modification that modulates gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the complexity and low heritability of this trait, it is difficult to increase the kidding number in a short period of time through traditional breeding methods. With recent technological advances, single nucleotide polymorphisms (SNPs) can be rapidly identified used as a marker in the construction of high-density genetic maps, precise localization of genes, and analysis of population genetic structure; moreover, SNPs have been used as effective molecular markers in goats and other species (Wang et al, 2022). Thus, these advances have clearly and unambiguously revealed the genetic structure of complex traits.…”
Section: Introductionmentioning
confidence: 99%